ConnecTF: A platform to integrate transcription factor–gene interactions and validate regulatory networks. Issue 1 (18th November 2020) - Brooks, Matthew D; Juang, Che-Lun; Katari, Manpreet Singh; Alvarez, José M; Pasquino, Angelo; Shih, Hung-Jui; Huang, Ji; Shanks, Carly; Cirrone, Jacopo; Coruzzi, Gloria M
Abstract: Deciphering gene regulatory networks (GRNs) is both a promise and challenge of systems biology. The promise lies in identifying key transcription factors (TFs) that enable an organism to react to changes in its environment. The challenge lies in validating GRNs that involve hundreds of TFs with hundreds of thousands of interactions with their genome-wide targets experimentally determined by high-throughput sequencing. To address this challenge, we developed ConnecTF, a species-independent, web-based platform that integrates genome-wide studies of TF–target binding, TF–target regulation, and other TF-centric omic datasets and uses these to build and refine validated or inferred GRNs. We demonstrate the functionality of ConnecTF by showing how integration within and across TF–target datasets uncovers biological insights. Case study 1 uses integration of TF–target gene regulation and binding datasets to uncover TF mode-of-action and identify potential TF partners for 14 TFs in abscisic acid signaling. Case study 2 demonstrates how genome-wide TF–target data and automated functions in ConnecTF are used in precision/recall analysis and pruning of an inferred GRN for nitrogen signaling. Case study 3 uses ConnecTF to chart a network path from NLP7, a master TF in nitrogen signaling, to direct secondary TF2 s and to its indirect targets in a Network Walking approach. The public version of ConnecTF (https://ConnecTF.org ) contains 3, 738, 278 TF–target interactions for 423 TFs in Arabidopsis, 839, 210 TF–target interactions for 139 TFs in maize ( Zea mays ), and 293, 094 TF–target interactions for 26 TFs in rice ( Oryza sativa ). The database and tools in ConnecTF will advance the exploration of GRNs in plant systems biology applications for model and crop species. Abstract : ConnecTF is a web application/database enabling users to build and validate gene regulatory networks by combining transcription factor–target binding and regulation datasets for model plants and crops.